Analysis of Border Crossing Inspection in Immigration Law at Class I Immigration Checkpoint Tanjung Perak Surabaya - Raden Satrio Wibowo; Siti Marwiyah; Wahyu Prawesthi (International Journal of Social Welfare and Family Law, 2026)
This research examines law enforcement against immigration violations and the factors influencing the effectiveness of border crossing inspection at the Immigration Checkpoint (TPI) of Tanjung Perak, Surabaya. Immigration inspection plays a vital role in safeguarding national sovereignty and monitoring cross-border human movement. Using a normative juridical approach with statutory and conceptual approaches, the findings demonstrate that enforcement procedures include document verification, identification of violations, administrative actions, and deportation in accordance with Law Number 6 of 2011 concerning Immigration. Common violations found include misuse of stay permits, travel document forgery, unauthorized border crossers, and illegal activities by foreign nationals beyond visa provisions. However, implementation still faces challenges such as limited human resources, inadequate infrastructure, and weak inter-agency coordination. Several factors affect the effectiveness of inspections, including personnel quality, technological support, legal frameworks, infrastructure capacity, traveler volume, inter-agency cooperation, political and international relations factors, socio-cultural dynamics, financial and logistical support, as well as internal supervision and accountability systems. The research concludes that institutional capacity building, policy integration, regulatory harmonization, and strengthened internal supervision are essential to ensure optimal immigration control at TPI Tanjung Perak in facing global challenges.